Efektivitas Ngaben Kremasi di Krematorium Bebalang Bangli - I Ketut Gede Pringgatama Bintang Mahasutra; I Putu Suyasa Ariputra (Sphatika: Jurnal Teologi, 2022)
This research is motivated by the condition of Balinese society which is increasingly modern with the influence of technology so that it has an impact on Balinese traditions and culture, especially the Ngaben Ceremony. Currently, conventional cremation ceremonies have been replaced with cremation cremations through crematoriums, one of which is the crematorium in the Bangli area, namely the Bebalang Crematrium. The crematorium cremation, which has many differences, raises questions about how effective the implementation of the crematorium cremation is and how the Pakraman village responds to the new tradition. This study also reveals the various reasons people have for holding a crematorium cremation ceremony. The purpose of the study was to determine the effectiveness of the Ngaben crematorium and the response of the Pakraman village in responding to changes in the Ngaben tradition. The research uses qualitative methods with a phenomenological approach, data collection through interviews, observations and literature studies. The results obtained in the study are that crematorium cremations are effective to be carried out in today's modern era which requires everything to be practical and efficient, Pakraman village The reason people choose to do Ngaben in the crematorium is also based on several factors including socio-cultural factors, social structure factors, factors economy, labor and time factors as well as certain condition factors in a region. So far, the awig-awig prevailing in Pakraman village does not limit the existence of crematorium cremations and the ceremony is adjusted to the times, not because an individual is subject to customary sanctions or other things. In carrying out the crematorium cremation, the Pakraman village community is also invited to attend as a symbol of harmony and maintain good relations between individuals and the community so as to minimize the risk of offence or misunderstanding.